World Bank Group and World Bank Corporate Scorecards, October 2015 - World Bank Group (World Bank, Washington, DC, 2015)
In July 2013, the World Bank Group launched its Strategy, outlining how it will partner more effectively with clients to help them achieve the ambitious goals of eradicating extreme poverty and boosting shared prosperity through economic growth, inclusion, sustainability and resilience. In April 2014, the World Bank Group Corporate Scorecard was launched for the first time and the World Bank Scorecard revised to monitor the implementation of the strategy. The World Bank Group Scorecard provides view of the results and performance indicators of the three World Bank Group institutions: the World Bank (WB), the International Finance Corporation (IFC), and the Multilateral Investment Guarantee Agency (MIGA). This brochure presents the scorecards, updated with the latest data available in fiscal year 2015. The scorecards are structured in three tiers. A tier one and two presents indicators monitoring aspects of growth, inclusiveness, and sustainability and resilience. Tier three captures the progress in implementing the World Bank Group strategy and includes measures of both operational and organizational effectiveness.